Surfing with the Spirit or sinking into the sea? : Elements enabling Christian character formation in a post-Christendom culture - Harrison, Mike (Ecclesial Futures, 2022)
This essay focuses on that dimension of sharing in the missio dei individually and corporately which involves the formation of Christian character. In particular what should be our first considerations when seeking character formation for participation in the missio dei? This article will suggest that our attention initially should be focused elsewhere than behaviour or direct attempts to change character. Further, while Aristotelian approaches are particularly popular in the contemporary (especially secular) literature, this essay considers the significance of dimensions of Christian character formation which are often underplayed by such approaches, not least loving attachment relationship to the divine and accountability-in-community. While space precludes an exhaustive account of influences on Christian character development, the essay considers aspects of experiencing Christ-centered community in shaping Christian character, utilising recent insights from the field of neuroscience. It concludes with an example taken from an Anglo-catholic setting of how eucharistic worship can contribute to the formation of Christian character and thus of sharing in the missio dei.